Characterization and Low-Resolution Structure of an Extremely Thermostable Esterase of Potential Biotechnological Interest from Pyrococcus furiosus - Mandelli, F.; Gonï¿½alves, T. A.; Gandin, C. A. [UNESP]; Oliveira, A. C.P.; Oliveira Neto, M. [UNESP]; Squina, F. M. (Springer Nature, 2016)
Enzymes isolated from extremophiles often exhibit superior performance and potential industrial applications. There are several advantages performing biocatalysis at elevated temperatures, including enhanced reaction rates, increased substrate solubility and decreased risks of contamination. Furthermore, thermophilic enzymes usually exhibit high resistance against many organic solvents and detergents, and are also more resistant to proteolytic attack. In this study, we subcloned and characterized an esterase from the hyperthermophilic archaeon Pyrococcus furiosus (Pf_Est) that exhibits optimal activity around 80ï¿½ï¿½C using naphthol-derived substrates and p-nitrophenyl palmitate (pNPP). According to the circular dichroism spectra, the secondary structure of P. furiosus esterase, which is predominantly formed by a β-sheet structure, is very stable, even after incubation at 120ï¿½C. We performed SAXS to determine the low-resolution structure of Pf_Est, which is monomeric in solution at 80ï¿½ï¿½C and has a molecular weight of 28ï¿½kDa. The Km and Vmax values for this esterase acting on pNPP were 0.53ï¿½mmol/L and 6.5ï¿½× 10−3ï¿½U, respectively. Pf_Est was most active in the immiscible solvents and retained more than 50ï¿½% in miscible solvents. Moreover, Pf_Est possesses transesterification capacity, presenting better results when isobutanol was used as an acyl acceptor (2.69ï¿½ï¿½ï¿½0.14ï¿½× 10−2ï¿½μmol/minï¿½mg) and the highest hydrolytic activity toward olive oil among different types of oils testes in this study. Collectively, these biophysical and catalytic properties are of interest for several biotechnological applications that require harsh conditions, including high temperature and the presence of organic solvents.
Keywords: Circular dichroism; Hyperthermophilic; kinetics parameters; SAXS; Transesterification